(untitled) (Research, Society and Development, 2022)
Specimens of Pectis elongata Kunth show variations in aromas when macerated, some accessions have cumin aroma (PCH), while others have lemongrass aroma (PCS). The objective of this work was to evaluate the morphoanatomical variations among these specimens and characterize them in these aspects. From fertile material with the same level of development, morphological records were made with Nankin drawings, following the usual techniques in the composition of boards for taxonomic purposes. Photomicrographs in photonic microscopy were obtained from histological slides of Organs vegetative stem and leaf organs, made freehand, following the usual techniques of plant anatomy. The PCH specimens showed a stem structure with six clearly highlighted sides, more elongated internodes and few ramifications; more developed leaves with fewer emergences on the margin; node with a smaller number of stipules when compared to a PCS sample, whose stem has shorter internodes, widely branched; smaller leaves with up to four emergences at the leaf base and a node with four stipules. The leaves are amphistomatic, with anisocytic stomata in both specimens, dorsiventral mesophyll and the presence of a Kranz sheath surrounding the vascular bundles and secretory cavities are more prominent in PCS specimens. The characterization at the morphological and anatomical level confirms other publications in the genus Pectis. The morphoanatomical variations are noticeable, however they are not diagnostic enough to state that they are different species, but there is strong evidence that they constitute different chemotypes.